Планування діяльності автотранспортного підприємства. Методичні аспекти - Ляшук, О. Л.; Плекан, У. М.; Цьонь, О. П.; Пиндус, Т. Б.; Lyashuk, О.; Plekan, U.; Tson, О.; Pyndus, Т. (ЦНТУ, 2022)
У статті обґрунтовано залежність ефективного функціонування автотранспортних підприємств від правильно сформованого плану розвитку на коротко- та довгострокову перспективу. Узагальнено науково-методичний інструментарій планування соціально-економічної діяльності автотранспортних підприємств. Запропоновано схему планування програми (проекту) соціально-економічного розвитку підприємств. Окреслено процеси формування карти результатів та рамки результатів як основних складових прогнозування подальшого соціально-економічного розвитку автотранспортних підприємств. The purpose of research is to analyze and summarize the main scientific and methodological aspects of planning socio-economic activities of motor transport enterprises. The article analyzes and summarizes the main scientific and methodological aspects of planning socio-economic activities of motor transport enterprises and substantiates the dependence of effective functioning of motor transport enterprises on a properly formed development plan in the short and long term. The scientific and methodological tools for planning the socio-economic activities of motor transport enterprises are generalized. A number of methods are described by which the activity of motor transport enterprises can be planned. In particular, the methods are analyzed: extrapolation, scenario creation, mental attack, factor analysis, forecasting by models of time series and leading indicators, methods of multifactor forecasting, expert evaluation, building a "tree" of decisions. The scheme of planning the program (project) of social and economic development of motor transport enterprises is offered. Stages of planning are presented, including: planning of works on improvement of separate kinds of activity, definition of interested parties, identification and analysis of potential problems, formulation of vision, formation of a map of results, formation of a framework of results. The documentation of each stage of planning is shown, including: drawing up of the plan (schedule) of works, schemes of interested parties, the list of priority problems, a tree of problems, the concept of vision of each of priority problems, maps of results on each of priority problems. enterprises. Since the stages of formation of the map of results and the general table of results of the project lay the foundation for the creation of a system of further monitoring of socio-economic development of the transport enterprise, the article pays special attention to these stages. Modern approaches to planning provide clarity of transformations of a single enterprise aimed at ensuring sustainable and dynamic development. Thus, the planning of the development of the motor transport enterprise provides an important mechanism for regulating socio-economic processes at the macro level.
Planning the Activities of the Motor Transport Enterprise. Methodological Aspects
Keywords: ефективність; управління; автотранспортне підприємство; соціально-економічний розвиток підприємства; методи планування; програма розвитку; efficiency; management; motor transport enterprise; social and economic development of the enterprise; planning methods; development program